Effect of fin-endwall fillet on thermal hydraulic performance of airfoil printed circuit heat exchanger. (5th October 2015) - Ma, Ting; Xin, Fei; Li, Lei; Xu, Xiang-yang; Chen, Yi-tung; Wang, Qiu-wang
Abstract: Printed circuit heat exchanger (PCHE) is recommended to be used for intermediate heat exchanger in Very High Temperature Reactor (VHTR). One of the key features is that it is manufactured by the photochemical etching in order to maintain the internal structure and metal properties. In this paper, a photochemical etching experiment is conducted to manufacture the airfoil PCHE plate. The result indicates that the airfoil fin is not an ideal airfoil profile, but has a fin-endwall fillet. For the purpose of simplifying the numerical model and saving computational time, a validated model with a single fluid is used to further study the effect of fin-endwall fillet on the thermal hydraulic performance of airfoil PCHE. It is found that the fin-endwall fillet can increase the heat transfer and pressure drop in the cases with the non-dimensional longitudinal pitch being 1.63. The effect of fin-endwall fillet on thermal hydraulic performance decreases with the increase of transverse pitch, but the longitudinal pitch has little effect when the non-dimensional longitudinal pitch is greater than 1.88. In the studied cases, the maximum difference of Nusselt number and friction factor between the two models with and without fin-endwall fillet is up to 6.7% and 6.4%. Highlights: Fillets are formed in the endwall of airfoil fins during the photochemical etching. Two-fluid model can be replaced by single-fluid model to perform simulation. Fin-endwall fillet can increase heat transfer and pressure drop at ζ l  = 1.63. Effect of fin-endwall fillet decreases as transverse pitch increases at ζ l  = 1.63. Longitudinal pitch has little effect at ζ l  ≥ 1.88.